Edukasi Diet Dan Latihan Diet Pada Pasien Hemodialisis Di Wilayah Kerja UPT Puskesmas Tanjung Rejo - Yusroq Prasetyo Pratama; Giri Susanto (Inovasi Kesehatan Global, 2024)
Chronic kidney disease is defined as kidney damage that lasts for a long time (chronic) and is characterized by a decrease in the ability of the kidneys to filter blood (Glomerular Filtration Rate/GFR). Patients with CKD often experience no symptoms or signs, until less than 15% of their kidney function remains. Since its early stages, CKD is closely related to the emergence of various complications, such as anemia, bone disease, etc. Hemodialysis is not a therapy to cure or restore kidney function, but it can prevent death more quickly in chronic kidney disease sufferers. The kidneys will still lose their ability for metabolic or endocrine activity so that patients with kidney failure must regularly undergo hemodialysis therapy obediently, which has an impact on the patient's quality of life. The aim is to implement nursing care for clients with chronic kidney failure on hemodialysis using diet education and exercise in the Tanjung Rejo Community Health Center UPT Work Area in 2023. This research uses a case study approach. Participant 2 was a kidney failure patient on hemodialysis at the Tanjung Rejo Community Health Center UPT. Data collection using interviews, observation and physical examination, documentation study and literature study. The instrument used in this research was a SGA form. After the data was collected, data analysis was carried out using the nursing process. The intervention provided diet education and diet training, then an evaluation was carried out. On the 3rd day after the evaluation the problem was resolved. The evaluation results show that nursing interventions providing diet education and diet training are very effective in maintaining the body condition of chronic kidney failure patients on hemodialysis. Conclusions and suggestions require efforts to involve the client's family to implement diet education with diet training so as not to worsen the disease they suffer from and can improve their quality of life.